Does relative age affect fame? Ask Wikipedia. Issue 3 (4th May 2021) - Peña, Pablo A.; Stephens-Davidowitz, Seth
ABSTRACT: We analyze whether age relative to school classmates affects the likelihood of becoming famous. We measure such likelihood as the ratio of Wikipedia entries to births, by state and date of birth, among people born in 1969–1988 in the US. Using a reduced-form Regression Discontinuity Design, we find evidence that men born after the Kindergarten cutoff date (i.e., relatively older) are roughly between 5 and 10 percent more likely to become famous, by Wikipedia standards, in comparison to those born before the cutoff (i.e., relatively younger). We don't find evidence of a similar effect for women.